Physiological and biochemical responses of drought-acclimated Pistacia atlantica Desf. to short-term irrigation - Toul, Fethi; Terfaya, Bouziane; Guenaia, Abdelkader (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Pistacia atlantica Desf. is a key drought-tolerant tree in hyper-arid North African ecosystems, yet little is known about how its osmolytes and phenolic-based antioxidant system respond when water availability is transiently improved. This study evaluated the short-term effects of irrigation on osmolyte levels, phenolic composition, and antioxidant activity in drought-acclimated P. atlantica trees. Ten adult trees in Igli region (southwestern Algeria) were assigned to non-irrigated and irrigated groups. Leaves were sampled before and after 90 days of irrigation. The relatively small sample size reflects the limited number of trees available and suitable for the study criteria in the area. Relative water content, proline, glycine betaine, total phenolics, and individual phenolics (HPLC-DAD) were determined. Results showed that irrigation increased leaf water content by about 12 % and significantly reduced proline (−25 %), glycine betaine (−22 %), and total phenolics (−30 %), while IC50 increased by 25 %. All quantified phenolics decreased after irrigation, with maximum reductions of −24 to −27 % were observed for chlorogenic, ferulic, and p-coumaric acids and quercetin, whereas gallic, syringic, ellagic acids and naringenin showed smaller declines (−8 to −16 %). The close coupling between osmolytes, key hydroxycinnamic acids and flavonols, and antioxidant activity indicates an integrated defence network that is highly sensitive to water availability and central to drought resistance and recovery in this species.